A Subset of CCL25-Induced Gut-Homing T Cells Affects Intestinal Immunity to Infection and Cancer - Fu, Hongmei; Jangani, Maryam; Parmar, Aleesha; Wang, Guosu; Coe, David; Spear, Sarah; Sandrock, Inga; Capasso, Melania; Coles, Mark; Cornish, Georgina; Helmby, Helena; Marelli-Berg, Federica M. (Frontiers in Immunology, 2019)
Protective immunity relies upon differentiation of T cells into the appropriate subtype required to clear infections and efficient effector T cell localization to antigen-rich tissue. Recent studies have highlighted the role played by subpopulations of tissue-resident memory (TRM) T lymphocytes in the protection from invading pathogens. The intestinal mucosa and associated lymphoid tissue are densely populated by a variety of resident lymphocyte populations, including αβ and γδ CD8+ intraepithelial T lymphocytes (IELs) and CD4+ T cells. While the development of intestinal γδ CD8+ IELs has been extensively investigated, the origin and function of intestinal TRM CD4+ T cells have not been clarified. We report that CCR9 signals delivered during naïve T cell priming promote the differentiation of a population of α4β7+ IFN-γ-producing memory CD4+ T cells, which displays a TRM molecular signature, preferentially localizes to the gastrointestinal (GI) tract and associated lymphoid tissue and cannot be mobilized by remote antigenic challenge. We further show that this population shapes the immune microenvironment of GI tissue, thus affecting effector immunity in infection and cancer.